Escherichia coli lipopolysaccharide induces alveolar epithelial cell stiffening. (23rd January 2019) - Oliveira, Vinícius Rosa; Uriarte, Juan José; Falcones, Bryan; Zin, Walter Araujo; Navajas, Daniel; Farré, Ramon; Almendros, Isaac
Abstract: Introduction: Application of lipopolysaccharide (LPS) is a widely employed model to mimic acute respiratory distress syndrome (ARDS). Available data regarding LPS-induced biomechanical changes on pulmonary epithelial cells are limited only to P. aeruginosa LPS. Considering that LPS from different bacteria could promote a specific mechanical response in epithelial cells, we aim to assess the effect of E. coli LPS, widely employed as a model of ARDS, in the biomechanics of alveolar epithelial cells. Methods: Young's modulus (E) of alveolar epithelial cells (A549) was measured by atomic force microscopy every 5 min throughout 60 min of experiment after treatment with LPS from E. coli (100 μg/mL). The percentage of cells presenting actin stress fibers (F-actin staining) was also evaluated. Control cells were treated with culture medium and the values obtained were compared with LPS-treated cells for each time-point. Results: Application of LPS induced significant increase in E after 20 min (77%) till 60 min (104%) in comparison to controls. Increase in lung epithelial cell stiffness induced by LPS was associated with a higher number of cells presenting cytoskeletal remodeling. Conclusions: The observed effects of E. coli LPS on alveolar epithelial cells suggest that this widely-used LPS is able to promote a quick formation of actin stress fibers and stiffening cells, thereby facilitating the disruption of the pulmonary epithelial barrier.